Analysis of Students' Mathematical Problem Solving Ability in terms of Student Learning Styles with Models Problem Based Learning - Dwi Ardy Dermawan; Pargaulan Siagian; Bornok Sinaga (BIRCU, 2021)
This study aims to analyze and determine: (1) the level of mathematical problem solving ability in terms of learning styles after implementing problem-based learning; (2) errors and difficultiesexperienced by students in solving math problem solving abilities in terms of learning styles after implementing problem-based learning. This research is a descriptive qualitative research. The subjects of this study were 32 students of SMA Negeri 1 Rantau Selatan class X MIPA 1, who were then appointed to interview subjects based on the Kolb & Kolb learning style, namely accommodation, divergent, assimilation, and convergent based on the level obtained based on indicators and aspects of difficulty. The research results are as follows: (1) there are 8 students (25%) has a learning style accommodation with the level of mathematical problem solving ability medium category amounted to 3 students, and low category amounted to 5 students; there are 11 students(34.37%) have a divergent learning style with a level of mathematical problem solving ability 1 student in high category, 4 students in medium category, 6 students in low category; exist 9 students (28.13%) have an assimilating learning style with a level of mathematical problem solving ability medium category amounted to 2 students, and low category amounted to 7 people; exist4 students (12.5%) have a convergent learning style with a level of mathematical problem solving ability medium category amounted to 3 students, with the low category amounted to 1 student;(2) for students' difficulties with accommodation learning styles, students have difficulty on principle indicators; for the difficulties of students with divergent learning styles, students have difficulty on indicators of concepts and principles; for the difficulties of students with assimilation learning styles, students have difficulty in the concept indicators and indicators of verbal problems; for the difficulty of students with convergent learning styles, students have difficulty on principle indicators.